2016
DOI: 10.20514/2226-6704-2016-6-1-34-39
|View full text |Cite
|
Sign up to set email alerts
|

Age and Gender Peculiarities of Development of Gallstone Disease

Abstract: Цель. Изучение роли факторов риска в механизмах желчного камнеобразования в зависимости от пола и возраста пациентов.Материал и методы. Обследованы 210 пациентов с I стадией желчнокаменной болезни (ЖКБ). В верификации диагноза использованы ре-зультаты ультразвукового исследования гепатобилиарной системы, многофракционного дуоденального зондирования с последующим ма-кроскопическим, микроскопическим, химическим и физическим исследованием желчи. В порциях «В» и «С» желчи определялась суммарная концентрация желчны… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
(4 reference statements)
2
2
0
3
Order By: Relevance
“…Based on this study, the most age occurred at the age above 40 years. This is in accordance with previous studies where most occur at the age of over 50 years (Hohlacheva, Sergeeva and Vahrushev, 2016). Based on this study, it was found that stones were most common in women, this is in accordance with previous studies (Kuy et al, 2013;Ahmad et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Based on this study, the most age occurred at the age above 40 years. This is in accordance with previous studies where most occur at the age of over 50 years (Hohlacheva, Sergeeva and Vahrushev, 2016). Based on this study, it was found that stones were most common in women, this is in accordance with previous studies (Kuy et al, 2013;Ahmad et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the classification of GSD by the Russian Gastroenterologists Association (2003), biliary sludge is an early manifestation of the disease, which is noted in its first (initial) stage (Hohlacheva et al, 2016). Therefore, in most cases, in the presence of biliary sludge, a drug correction is required, for example with UDCA preparations.…”
Section: Efficiency and Safety Studiesmentioning
confidence: 88%
“…В желчи определялась суммарная концентрация желчных кислот -ЖК ж, холестерина -ХС ж [9], вычислялся индекс литогенности желчи -холатохолестериноввй коэффициент (ХХК ж) . По методике, разработанной для слюны [10] На ранней стадии ЖКБ у молодых людей метаболизм экзогенного холестерина происходит медленнее, у пожилых -снижается активность 7-альфа-гидроксалазы, участвующей в синтезе желчных кислот из холестерина [11,12]. Нами получены аналогичные данные: в 1-й группе литогенность желчи главным образом связана с повышенным уровнем ХСж, в 3-й группе -со сниженным уровнем ЖКж, во 2-й группе -эти процессы относительно уравновешены.…”
Section: материал и методыunclassified